2020
DOI: 10.1177/2050168420923870
|View full text |Cite
|
Sign up to set email alerts
|

Sedation or General Anaesthetic for Special Care Patients?

Abstract: When faced with an anxious patient with complex needs who requires dental care, it can be difficult to decide on the most appropriate method to manage their pain and anxiety. There are a range of conscious sedation techniques that may be used, and on some occasions, general anaesthesia may be required. This paper describes the methods available and the factors influencing the decision-making process. The general dental practitioner (GDP) may not be able to offer care in their setting, but knowing more about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(6 reference statements)
0
1
0
Order By: Relevance
“… 7 Additionally, depending on the patient and treatment needs, several routes of administration for dental sedation may be used: inhalation, intravenous, oral, intranasal and intramuscular. 8 A survey of dentists in the United States and Canada has revealed that 75.7% regularly use conscious sedation in practice; half reported using sedation as many as six times per month, and the other half reported using sedation more than six times per month. 9…”
Section: Introductionmentioning
confidence: 99%
“… 7 Additionally, depending on the patient and treatment needs, several routes of administration for dental sedation may be used: inhalation, intravenous, oral, intranasal and intramuscular. 8 A survey of dentists in the United States and Canada has revealed that 75.7% regularly use conscious sedation in practice; half reported using sedation as many as six times per month, and the other half reported using sedation more than six times per month. 9…”
Section: Introductionmentioning
confidence: 99%